Cyber-physical systems: a case study of development for manufacturing industry. (2017) - Choi, SangSu; Kang, Gyhun; Jun, Chanmo; Lee, Ju Yeon; Han, Seukjoo
Manufacturing industry worldwide is now faced with various issues such as diversification of customers' need, rising labour costs, soaring energy resources costs, environmental pollution, and escalating uncertainties. To resolve these issues, global manufacturing enterprises and developed countries are leading the development of Smart Manufacturing System (SMS). Smart Manufacturing (SM) connects all of procurement, production, logistics, service, and product to the network, and controls the entire production processes in real-time on the basis of unified environment of Cyber-Physical Systems (CPS). CPS for manufacturing enables optimisation of product development and total control of production system through real-time exchange of all information required for production based on Internet of Things (IoT). In order to establish CPS in manufacturing companies, legacy systems and engineering tools need to be connected to cloud computing and IoT, and real-time information exchanges from the shop-floor level to the business level need to be enabled. This paper investigates current issues of a CPS application in manufacturing enterprises and introduces a CPS development case based on IoT platform Thingworx and a reference model.